A Study the Concepts and Morals That Appear in The Youth Literature Of Nai In Award "Ordinary Boy in The Land of Magic" - Thobpae, Paweena; Phapor, Phatthanant; Promkantha, Paphitchaya (Journal of Thammawat, 2023)
Research on this subject in the objective 1) to study the concepts in the Nai In Award Youth Literature, "Ordinary Boys in the Land of Magic" and 2) to study the moral principles that appeared in the Nai In Award Youth Literature, "Ordinary Boys in the Land of Magic". The researcher studied the research papers concerning the concepts and principles of morality and ethics in youth literature Nai In Award for "Ordinary Boys in the Land of Magic", Analyze, summarize, and discuss the findings of the descriptive research findings. The results of the research showed that : Regarding the concepts Nai In Award Youth Literature, "Ordinary Boys in the Land of Magic", a total of 15 chapters, appears in 4 concepts: 1) Conceptual concepts, 2)behavioral concepts, 3) visual concepts and events and 4) the expression of emotions. In terms of morals, and ethics as appeared in the youth literature, Nai In Awards "Ordinary Boys in the Land of Magic" consists of 15 episodes, consisting of 12 aspects. The most common thing is compassion, followed by courage, courage, unity, patience, selflessness, discipline, individuality, gratitude, honesty. And the least solitude is perseverance. "Ordinary boys in the land of magic" Is a youth literature with important content Is a presentation about the awareness of the importance of nature. We have to help maintain and maintain a lasting existence. In addition, it also includes insights into the main moral principles and practices living together, happily in society with other people Youth can bring ideas and the moral in the content to be adapted to be useful in daily life.